The Importance of Growing Middle School Youth Resilience on Bullying Behavior: Literature Review - Hasanah, Uswatun; Rini, Rr. Amanda Pasca (International Journal of Social and Management Studies, 2023)
Cases of bullying often occur among adolescents, especially junior high school students where friendship is very important. If adolescent fail to interact socially then these adolescents are likely to become victims of bullying behavior from other adolescent. Bullying has a negative impact on the victim's mental health, such as anxiety, depressive symptoms, and suicide attempts. However, some adolescents who are able to recover from negative experiences (bullying) show self-resilience which is called resilience. Resilience is influenced by protective factors internally and externally. The purpose of this paper is to find out how to deal with bullying behavior with resilience and factors that can foster resilience in junior high school students who are victims of bullying. The method used is a literature review design, by collecting articles through Google search, ResearchGate, and Google Scholar. Based on the articles collected, the results show that students need to increase self-resilience, which can be done by being open to parents/friends about the incidents of bullying they are experiencing and trying to regulate their emotions and behavior. The level of resilience students have as a result of bullying victims can also be influenced by the surrounding environment. Warmth, emotional bond, and support from parents, friends and teachers are factors that can protect victims of bullying